Sailor Moon. 12 - Takeuchi, Naoko (New York: Kodansha Comics)
As Galaxia picks off one Sailor Guardian after another, even those of the outer planets, Usagi finds new companions to help her fight her most nefarious enemy yet
Keywords: Young adult fiction